EFFECTS OF SIMVASTATIN AND LEVO-CARNITINE ON PLASMINOGEN ACTIVATOR INHIBITOR-1 LEVELS IN OBESE INSULIN RESISTANT RATS - Saeed, Gul-e-Naghma; Butt, Idrees Farooq (Pakistan Journal of Physiology, 2015)
Insulin resistance is considered to be the underlying pathophysiology of the obesity-related cardiovascular risk factors in metabolic. The role of lipid lowering drugs in the treatment of insulin resistant states and metabolic syndrome is significant. Objective of the present study was to determine the effects of Simvastatin and L carnitine, individually and in combination, on plasminogen activator inhibitor-1 levels as Cardiac Risk Factor in obese insulin-resistant Sprague-Dawley (SD) rats. Methods: Eighty healthy SD rats were divided into 5 groups of 16 rats each. Group-1 was given normal pellet diet and served as control while the rest were given high fat diet (HFD) to induce obesity. After two months of HFD, insulin resistance was confirmed and drug administration was carried out for one month in groups 3, 4 and 5 while group-2 served as control for them. At the end of this period, Plasminogen activator inhibitor-1 level was measured. Results: Plasminogen activator inhibitor-1 (PAI-1) levels were raised significantly in the group given HFD (11.78±3.58 ηg/ml from 2.66±1.80 ηg/ml in Group 1, p<0.001). Compared to HFD group 2, PAI-1 levels were significantly decreased in both simvastatin (5.80±1.65 ηg/ml, p<0.05) and combination therapy group (6.315±1.88 ηg/ml, p<0.05) but decrease was statistically insignificant in carnitine monotherapy group (10.20±1.8 ηg/ml). Conclusion: The combination therapy of simvastatin and levo-carnitine resulted in greater improvement in plasma PAI-1 levels as a cardio vascular disease risk factor in diet induced obesity than either of the drugs alone.